1998
DOI: 10.1037/0894-4105.12.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Bihemispheric processing of redundant bilateral lexical information.

Abstract: Cerebral asymmetries in lexical ambiguity resolution were studied. In 2 experiments, targets related to the dominant and subordinate meanings of ambiguous word primes were presented for lexical decision after a 750-ms stimulus onset asynchrony. Experiment 1 compared presentation of target words to the left visual field/right-hemisphere (LVF/RH), to the right visual field/left-hemisphere (RVF/LH), or after redundant bilateral visual field (BVF) presentation. Experiment 2 examined unilateral priming in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 35 publications
4
46
2
Order By: Relevance
“…The biasing context findings are consistent with the pattern across neuropsychological studies, which have suggested that both LH and RH damage interfere with normal meaning selection (e.g., Grindrod and Baum, 2003;Swaab et al, 1998;Tompkins et al, 2000), and are also consistent with recent neuroimaging findings of bilateral activation during ambiguity resolution (Rodd, Davis, and Johnsrude, 2005;Zempleni, Renken, Hoeks, Hoogduin, and Stowe, 2007). For unbiased contexts, our N400 findings conflict with the reaction time effects that Burgess and Simpson (1988) found for a lexical decision task at a long (750 ms) SOA, but are consistent with the accuracy effects that Hasbrooke and Chiarello (1998) observed for a comparable lexical decision task with the same SOA: the LH showed activation for multiple meanings, whereas the RH only showed activation for the dominant meaning. Interestingly, if one compares the behavioral priming effects at the 35 and 750 ms SOAs utilized by Burgess and Simpson to the N400 and LPC priming effects observed in the current study, the pattern of activated meanings is identical (with the exception that we did not observe late LH inhibition of the subordinate meaning): each study found early activation of both meanings in the LH, along with early dominant activation and late activation of both meanings in the RH.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The biasing context findings are consistent with the pattern across neuropsychological studies, which have suggested that both LH and RH damage interfere with normal meaning selection (e.g., Grindrod and Baum, 2003;Swaab et al, 1998;Tompkins et al, 2000), and are also consistent with recent neuroimaging findings of bilateral activation during ambiguity resolution (Rodd, Davis, and Johnsrude, 2005;Zempleni, Renken, Hoeks, Hoogduin, and Stowe, 2007). For unbiased contexts, our N400 findings conflict with the reaction time effects that Burgess and Simpson (1988) found for a lexical decision task at a long (750 ms) SOA, but are consistent with the accuracy effects that Hasbrooke and Chiarello (1998) observed for a comparable lexical decision task with the same SOA: the LH showed activation for multiple meanings, whereas the RH only showed activation for the dominant meaning. Interestingly, if one compares the behavioral priming effects at the 35 and 750 ms SOAs utilized by Burgess and Simpson to the N400 and LPC priming effects observed in the current study, the pattern of activated meanings is identical (with the exception that we did not observe late LH inhibition of the subordinate meaning): each study found early activation of both meanings in the LH, along with early dominant activation and late activation of both meanings in the RH.…”
Section: Discussioncontrasting
confidence: 42%
“…Thus, it appears that RH processing may prevail when a less frequent meaning is being processed. However, rather than maintaining less frequent meanings (Burgess and Simpson, 1988), as proposals such as coarse coding would suggest, it seems that the RH may tend to select the dominant meaning (Hasbrooke and Chiarello, 1998). Dominant meaning selection is most consistent with models of lexical access that incorporate effects of meaning frequency, such as the ordered access (Hogaboam and Perfetti, 1975) and reordered access models (Duffy et al, 1988); nevertheless, both selective access (Swinney and Hakes, 1976) and exhaustive access (Swinney, 1979) models would also predict that the dominant meaning would eventually be selected when biasing contextual information is unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is even more remarkable considering that the authors scored responses within 200-1,800 ms as correct, although latencies slower than 1,000 ms (or 2SD) are generally regarded as delays and discarded from analyses (e.g. de Gelder et al 2001;Hasbrooke and Chiarello 1998;Koivisto 2000;Marzi et al 1996;Miniussi et al 1998;Mordkoff and Miller 1993). Furthermore, even though stimulus eccentricity was only 2.9°, Schweinberger and colleagues did not provide any control for eye movements.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the RTE has been shown using simple flashes (Corballis 2002;Savazzi and Marzi 2002), checkerboards (Miniussi et al 1998), shapes and colours (Mordkoff and Yantis 1993), letters (Grice and Reed 1992;Mordkoff and Miller 1993), and letterstrings (Marks and Hellige 1999), on healthy subjects as well as on neurological patients (with hemianopia and blindsight: de Gelder et al 2001;Marzi et al 1986;hemispherectomy: Tomaiuolo et al 1997;split-brain: Corballis 1995;Forster and Corballis 2000;Iacoboni et al 2000;Mohr et al 1994;Reuter-Lorenz et al 1994;Corballis 2002, 2003;and visual extinction: Marzi et al 1996). In normal viewers the RTE has also been demonstrated with meaningful stimuli such as words (Hasbrooke and Chiarello 1998;Mohr et al 1996), numbers (Ratinckx and Brysbaert 2002), drawings of animals or objects (Koivisto 2000), and familiar neutral faces (Mohr et al 2002). Likewise, direct tests have often shown violations or race models, thereby providing support for models based on neural coactivation and interhemispheric summation (Corballis 2002;Grice and Reed 1992;Iacoboni et al 2000;Iacoboni and Zaidel 2003;Marzi et al 1996;Miller 1982Miller , 1986Miniussi et al 1998;Mordkoff and Yantis 1993;Reuter-Lorenz et al 1994;Savazzi and Marzi 2002).…”
Section: Introductionmentioning
confidence: 99%